Für eine Handvoll Dollar - Leone, Sergio 1929-1989; Catena, Victor Andres 1925-2009; Morricone, Ennio 1928-2020 (Universum Film, 2013)
A wandering gunfighter plays two rival families against each other in a town torn apart by greed, pride, and revenge. (www.imdb.com)